Impact of Parents' Comprehensive Health Literacy on BMI in Children: A Multicenter Cross‐Sectional Study in Japan. (4th November 2018) - Nakamura, Daisuke; Ogawa, Masato; Nakamura, Teruhiko; Izawa, Kazuhiro P.
ABSTRACT: BACKGROUND: Low‐functional health literacy (HL) of parents influences poor child health outcomes. This study aimed to assess the relationship between comprehensive HL of parents and body mass index (BMI) of their children. METHODS: We enrolled 3‐ to 6‐year‐old preschool‐aged children and their parents in this multicenter cross‐sectional cohort study. We evaluated parents' comprehensive HL with the 14‐item HL scale. Children's BMI categories were defined using International Obesity Task Force cutoffs according to age and sex. We analyzed differences in data between the high‐HL group and the low‐HL group and investigated the association between HL of parents and their children's BMI by multivariate logistic regression analysis. RESULTS: The high‐HL group comprised 208 (75.1%) children and the low‐HL group comprised 69 (24.9%) children of whom 23 (8.3%) were overweight and 35 (12.6%) were thin. The low‐HL group had more children with poor BMI than the high‐HL group. Multivariate analysis showed an association between the low HL of parents and the poor BMI of their children after adjustment for all other confounding factors. CONCLUSIONS: Comprehensive HL of parents appears to affect the BMI of their children independently, suggesting that interventions to improve HL in parents are necessary.